The Impact of Digital Marketing on Parent-Child Relationships and Family Dynamics - Bouakaz, Laid (Journal of Posthumanism, 2025)
Digital marketing influences our purchasing choices and restructures family relationships in today’s highly connected digital world. This article explores the hidden yet substantial influence digital marketing experts on parental-child relationships. The digital environment is transforming family life through its impact on materialistic mindsets and emotional connections and parental roles. A qualitative thematic approach is used to examine recent literature from 2014 to 2024 to reveal five essential findings about digital family interactions and their effects on children’s values and parental-child relationships. The study explores the dual nature of digital marketing as it functions as both a communication link and an obstacle in family relationships. The research shows promising developments even though genuine risks exist in the form of screen dependency and consumer pressure and emotional distance. Active parental involvement combined with boundary setting and open media discussions enables digital marketing to function as a connection builder instead of a source of conflict. The article demonstrates that families need a balanced approach which combines digital literacy education with parental involvement and supportive policies to succeed in an algorithm-driven world.